WEB Device for Endovascular Treatment of Wide-Neck Bifurcation Aneurysms - Lubicz, B. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: The WEB is an intrasaccular flow disrupter dedicated to EVT of IA. We report our initial experience in a series of patients treated with this device. MATERIALS AND METHODS: This prospective study was approved by the authors' ethical committees. Nineteen patients with 20 unruptured wide-neck bifurcation IAs were treated by WEB placement. Technical issues, immediate posttreatment angiographic findings, and clinical and imaging follow-up at 3, 6, and 12 months were assessed. RESULTS: Failure of WEB placement occurred in 1 case because of unavailability of a suitably sized device. Embolization was successful in 18 patients with 19 IAs, and it required additional stent placement and/or coiling in 3 cases at the acute phase and in 1 case at follow-up. Two patients experienced a symptomatic complication, and 16 patients had normal neurologic examination findings at discharge. Immediate anatomic outcome showed 1 complete occlusion, 13 near-complete occlusions, and 5 incomplete occlusions. At follow-up, 17 patients had normal neurologic examination findings and 1 retained a hemiparesis. Angiographic controls were obtained in all patients (mean, 6 months), and they showed stable or improved results in all except 4 cases, including 2 complete occlusions, 15 near-complete occlusions, and 2 incomplete occlusions. CONCLUSIONS: In this initial series of patients, EVT of wide-neck bifurcation IAa with the WEB was feasible. Further studies are needed to evaluate the indications, safety, and efficacy of this new technique.